DINAMIKA POPULASI HAMA DAN PENYAKIT UTAMA PADA TANAMAN CABAI MERAH (Capsicum annuum L.) DI KOTA PALANGKA RAYA - Agustini, Sri; Redin, Herry; Kulu, Ici Piter; Amelia, Vera; Surawijaya, Panji; Ludang, Yetrie (Agrienvi: Jurnal Ilmu Pertanian, 2023)
Pests and disease are one of the factors that cause yield loss of red chilli. Knowledge of the population dynamics of the main pests and diseases of red chilli can be used as the basis for recommendations for pest and disease control. The research aims to analyze pests and diseases population dynamics on red chilli cultivation, the influence of environmental factors and the influence of population dynamics on red chilli production. This research was conducted in Kereng Bangkirai Village Sebangau District, Kalampangan Village Sebangau District and Tanjung Pinang Village Pahandut District, Palangka Raya City. The research was conducted from December 2022 to March 2023. The research using a quantitative descriptive method. The sample plants used the diagonal plot sampling method, with an area of 4 m x 4 m. Observation were made in the morning once a week from transplanting to harvesting. The result showed that the dynamics of the main pest population of red chilli plants was influenced by the availability of food, the population of red chilli pests was high when the condition of the plant organs (leaves) was still at a young age which was suitable for its feed designation, the dynamics of anthracnose disease was influenced by temperature and humidity; Temperature and humidity do not always have a significant effect on pest and disease population dynamics. Fluctuating pest populations are influenced by the cultivation system applied by farmers, especially the use of synthetic pesticides; The higher number of pest and disease populations cause less production of red chilli plants.